Human rights, advocacy and special needs education (2011)
The term human rights and advocacy have been carefully defined and properly positioned in this paper. In addition, what special needs people are all about is discussed with factors that interfere with their human rights. Furthermore, the paper presented an overview of advocacy for children with special needs education. Finally, the paper highlighted the measures for promoting and safeguarding human rights, advocacy and special needs education in Nigeria.